Rendere eterno l’istante: misticismo e realismo nel Velázquez di María Zambrano e José Ortega Y Gasset - Tartabini, Veronica (B@belonline, 2021)
Miguel de Unamuno with his poetics of the Christ located in El Prado and Foucault with his philosophical analysis of the Meninas, are two perspectives that tried to address the achieved utopia of the art of Diego Rodríguez de Silva and Velázquez, but they were not the only ones. We speak of no-place because in his brushstrokes dedicated to both secular and religious themes, we can perceive what only a refined exponent of the paradoxical cultural essence of Spain could achieve: to make the moment eternal by recognizing the mystical value of reality, the sacredness that seemingly insignificant everyday circumstances await. María Zambrano and José Ortega y Gasset, with the tools of Spanish thought, were able to decipher this enigma that embodies the spirituality of Spanish realism. In the Madrid of the Habsburgs, the Cartesian methodical doubt and the imperfection of Caravaggio’s human and baroque reality converge.